A hybrid overlay architecture for social feature integration in browser-based cloud gaming - Shah Ahmad Shahrizal, Ahmad Nur Zafran; Mohammad, Danish Haikal; Attarbashi, Zainab; Hasan Alamrami, Amal Abdulwahab; Maspo, Nur-Adib (IIUM Press, 2026)
Current cloud gaming platforms force a trade-off between streaming performance and integrated social features, typically requiring resource-intensive dedicated clients. This paper presents an architecture that eliminates this compromise through a Hybrid Overlay engine. Built with vanilla TypeScript/HTML5 and decoupled from the WebRTC video pipeline, the engine renders social overlays (chat, friend lists) directly onto the game canvas, avoiding DOM overhead. A Rust/Actix-web backend ensures low-latency streaming. The system was validated through comprehensive testing. Performance and security tests confirmed: automatic streamer binary compilation, successful WebRTC stream initiation, automated SSL generation, and strict HTTPS enforcement. Functional tests demonstrated robust authentication (registration, session persistence), real-time message synchronization (<200ms), and correct social workflows. Crucially, the input sandbox isolated chat keystrokes from the game stream, and Firebase RBAC rules blocked all unauthorized data writes. By unifying high-fidelity streaming with lightweight, native social integration, this work provides a performant, zero-install platform that makes social cloud gaming accessible on low-end devices, establishing a new model for architecting these services